Modelling the influence of frequency in a low pressure capacitively coupled hydrogen discharge - Marques, L. (2002)
This paper investigates the dependence of plasma density and self-bias voltage with excitation frequency (13.56-40.68 MHz) using a two-dimensional (2D) fluid model in a low pressure (300 mTorr) radio frequency (RF) capacitively coupled hydrogen discharge. A comparison with experimental results reveals that the model predicts the correct trends of density and self-bias voltage variation with driving frequency